Antitumor and Immunopotentiating Activity of Polysaccharide PST001 Isolated from the Seed Kernel of Tamarindus indica: An InVivo Study inMice - Aravind, S. R.; M. Joseph, Manu; Varghese, Sheeja; Prabha, Prabha; Sreelekha, T. T. (Hindawi Publishing Corporation, 2012)
Antitumor activity of polysaccharide PST001 isolated from the seed kernel of Tamarindus indica was evaluated using different cancer cell lines. Human cancer cell lines A549, KB, and MCF-7 and murine cancer cell lines DLA and EAC were treated with PST001 and cell growth inhibition was assessed by MTT assay. In vivo studies were carried out for toxicity, tumor reduction and immunomodulation. The respective IC50 of PST001 in A549, KB, and DLA was at 80.72, 190.99, and 91.14 μg/mL. Significant tumor reduction was obtained in both DLA and EAC tumors on treatment with PST001 which was more prominent when PST001 was administered with CTX/5-fluorouracil. Increase in total WBC, CD4+ T-cell population, and bonemarrow cellularity suggested strong immunomodulatory activity for this compound. No significant abnormality was observed in toxicity studies. Thus the results of the present study suggest that PST001 has immunomodulatory and tumor inhibitory activities and has the potential to be developed as an anticancer agent and immunomodulator either as a sole agent or as an adjuvant to other chemotherapeutic drugs.